Implementation of Li-Fi based home automation system - Rahman, Tareq; Refat, Rafiul Islam; Ahmed, Faiyaz (Brac University, 2023)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.